Assessing the Impact of Islamic Teachings on the Rights and Welfare of Muslim Women: A Policy and Social Justice Perspective - Mohammed Houmine (Religion and Policy Journal, 2024)
Research Problem: The rights and responsibilities of women in Islam have often been misunderstood, particularly in the international context. Predominant narratives from Western societies frequently depict Muslim women as oppressed and lacking gender equality. This study investigates a fundamental question: has Islamic teaching contributed to the social welfare of Muslim women by granting them equitable rights and responsibilities?